PREDICTION OF SEISMIC GROUND MOTION IN THAWING PERMAFROST AREAS - Dzhurik V.I.; Drennov A.F. (My University, 1996)
Based on direct geophysical measurements and theoretical calculations a new approach was developed to the prediction of maximum seismic ground motion in areas with disturbed permafrost soils. This approach was implemented at the construction site of the second unit of the Bilibino nuclear power station. This work revealed some general patterns in the variation of seismic velocities and ground motion parameters during a predicted large earthquake in degraded permafrost.